2008
DOI: 10.1021/bi8010658
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of the Plasmodium falciparum Chloroquine Resistance Transporter with a Novel Perfluorophenylazido Chloroquine

Abstract: Several models describing how amino acid substitutions in the Plasmodium falciparum chloroquine resistance transporter (PfCRT) confer resistance to chloroquine (CQ) and other antimalarial drugs have been proposed. Further progress requires molecular analysis of interactions between purified reconstituted PfCRT protein and these drugs. We have thus designed and synthesized several perfluorophenyl azido (pfpa) CQ analogues for PfCRT photolabeling studies. One particularly useful probe (AzBCQ) places the pfpa gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(124 citation statements)
references
References 30 publications
9
112
3
Order By: Relevance
“…It has been shown previously that a tertiary amine in this position impacts the activity of CQ analogues, as it influences the diffusion of the compounds in the digestive vacuole (19,20). Ethyl amine compound 21a was first connected to a C 3 linker, using chloroiodopropane (compound 33), leading to chloropro- Table S2 in the supplemental material for SEM and statistics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that a tertiary amine in this position impacts the activity of CQ analogues, as it influences the diffusion of the compounds in the digestive vacuole (19,20). Ethyl amine compound 21a was first connected to a C 3 linker, using chloroiodopropane (compound 33), leading to chloropro- Table S2 in the supplemental material for SEM and statistics).…”
Section: Resultsmentioning
confidence: 99%
“…3). The 4-aminoquinoline scaffold has been shown to be essential for the binding of CQ to free heme (18), and both the terminal tertiary amino group and the basicity of the quinolyl nitrogen are key elements (19,20). Ideally, the length of the aliphatic side chain should be 2 to 4 carbons; however, the methyl group has little influence on the activity and was thus not retained.…”
mentioning
confidence: 99%
“…An earlier study identified the vacuolar loop between putative transmembrane domains 9 and 10 as part of the PfCRT-binding site for AzBCQ, a CQ analog and photoaffinity label (42). Binding of the affinity label was competitively inhibited by QN, suggesting overlap in their respective binding sites.…”
Section: Discussionmentioning
confidence: 97%
“…Scatchard analysis indicated a single-drug binding site in PfCRT, and, surprisingly, that CQS and CQR isoforms of PfCRT have similar affinity for CQ (K d ¼ 435 and 385 nM, respectively). A recent follow-up study of CQ binding used covalent attachment of a perfluoroazidotagged CQ probe to quantify CQ probe binding versus other quinoline antimalarials and to further define the drug binding site in PfCRT, which is predicted to be disposed towards the DV side of the DV membrane (Lekostaj et al 2008). Satisfyingly, this binding site can also easily place the quinoline ring of CQ near mutations in PfCRT isoforms that are known to modulate response to drugs (Fidock et al 2000b;Cooper et al 2002).…”
Section: Vesicle Studiesmentioning
confidence: 99%
“…Satisfyingly, this binding site can also easily place the quinoline ring of CQ near mutations in PfCRT isoforms that are known to modulate response to drugs (Fidock et al 2000b;Cooper et al 2002). It is clear at this point that both wild-type (CQS) and mutant (CQR) isoforms of PfCRT bind CQ at a single-drug binding site, that related quinoline drugs such as MQ and QN compete with CQ for binding to this site, and that chemoreversal agents such as VPL inhibit CQ binding only for some PfCRT isoforms (Lekostaj et al 2008).…”
Section: Vesicle Studiesmentioning
confidence: 99%